2023
DOI: 10.1177/17455057231170973
|View full text |Cite
|
Sign up to set email alerts
|

Social engagement and loneliness in school-age autistic girls and boys

Abstract: Objectives: This study examines the relationship between social engagement and loneliness in female and male autistic children and adolescents in school-based social settings. Secondary aims sought to explore the emergence of loneliness across different age groups and differences in social engagement and loneliness between genders. Methods: This study conducted an analysis of previously collected data from two multi-site randomized control trials. This study included 58 autistic students (29 females, 29 males)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The other student had a very similar response, indicating that the image reminded her of a feeling of being "isolated and misunderstood". The sense of isolation and loneliness has been reported in other research [35,36], with suggestions that autistic students may experience more loneliness in inclusive settings. However, these outcomes may also be related to both teachers and students having lower expectations of socialization for autistic students.…”
Section: Theme Three: the Influence Of Conceptions Of Autism On Expec...mentioning
confidence: 54%
See 1 more Smart Citation
“…The other student had a very similar response, indicating that the image reminded her of a feeling of being "isolated and misunderstood". The sense of isolation and loneliness has been reported in other research [35,36], with suggestions that autistic students may experience more loneliness in inclusive settings. However, these outcomes may also be related to both teachers and students having lower expectations of socialization for autistic students.…”
Section: Theme Three: the Influence Of Conceptions Of Autism On Expec...mentioning
confidence: 54%
“…It is difficult to determine if this teacher's response is influenced by lived experience and/or by popular autism culture, but there are multiple examples of images of autistic children on the internet looking isolated from others. The teacher's response is problematic as it generalizes the conception that autistic students prefer to be alone when research indicates they report feeling isolated and lonely, as indicated by the students in this research [35,36]. Rather than believing these students are happy in this state, attention to explicit support in developing friendships may be beneficial [37,38].…”
Section: Theme Three: the Influence Of Conceptions Of Autism On Expec...mentioning
confidence: 85%